Cuestiones sobre Stalin - Hermida Revillas, Carlos (Historia y Comunicación Social, 2005)
Stalin has been object of all kind of vilification and he has been severely criticized in all the aspects of his political career. Most historians consider him as an incarnation of evil similar to Hitler. Nevertheless, a dipassionate analysis of his work shows that shades and lights. Except those who see history with blinders, nobody could deny the enormous, scientific and cultural development experienced by the URSS in the thirty years of quinquenial plans proposed by Stalin. It is also impossible to deny the trascendental role played by the Soviet Union in the defeat of Nazism during the Second World War. Besides these expressions of success, there is also the sombre aspect of the repression of the bolshevist party. This paper tries to focus in some aspects of the Stalinist politics different from what is usually offered by the books of history. It as aimed at the need of reinterpreting the history of Stalin away from the platitudes present in the historiography of the topic. We do not pretend to justify anything, but to show the facts are more complex than what some historians want us to believe.